Tingkat Kepatuhan Wajib Pajak UMKM Di Jawa Timur, Indonesia - Setiadi Alim Lim; Lilik Indrawati (BIP's JURNAL BISNIS PERSPEKTIF, 2018)
Micro, small and medium-sized enterprises play an important role in national economic development in many countries around the world. Micro, small and medium-sized enterprises have a large contribution to GDP (Gross Domestic Product), the supply of employment and exports of a country. Although it has a large contribution to the national economy, the contribution of micro, small and medium-sized enterprises to the state income from the tax sector is very small. There is a tendency for voluntary tax compliance from micro, small and medium- sized enterprises to be very low. This research aims to study the level of micro, small and medium-sized enterprises of tax compliance in East Java, Indonesia. To measure the level of tax compliance, 3 indicators are used, namely the ownership of the Taxpayer Identification Number (TIN), compliance with paying Income Tax and compliance to fill out and report the Annual Income Tax Return. The results showed that the level of tax compliance in micro, small and medium enterprises in East Java, Indonesia was still very low. Micro, small and medium-sized who have a Taxpayer Identification Number (TIN) is only 37.80%, those who pay Income Tax are only 21.95% and those who fill and report Annual Income Tax Returns of only 18,29%.